Regulations Government Moderate the Influence of Price and Brand Image on Interest in Buying Electric Cars in the Mebidang Metropolitan City (Medan-Binjai-Deli Serdang) - Satria Tirtayasa; Hasmanan Khair; Yuni Satria (Universitas 17 Agustus 1945 Semarang, 2023)
Research objectives: To analyze and know the role of the government in regulating the government's moderate influence on price, facilities, and brand image towards interest in buying electric cars and electricity in the Mebidang Metropolitan City (Medan-Binjai-Deli Serdang). Population from study This is a candidate interested consumers buying car electricity at electricity in the Mebidang Metropolitan City (Medan-Binjai-Deli Serdang). Because the population amount is unknown, the researcher determines the sample size using the Lemeshow formula, which amounts to 384 respondents. Sample determination using purposive sampling, i.e., candidate consumer Already owns a car, income >= 10 million rupiah. Data was obtained with a questionnaire online via Google Forms. Hypotheses are tested using validity test methods, reliability tests, assumption tests classic, regression multiplex, and hypothesis testing with SPSS. Based on the results, Price research matters positively and significant to Purchase Interest, Facilities influential positively and significant to purchase intention, brand image is influential positive and significant to Purchase Intention, Brand Image are influential positive and significant to Purchase Interest, Regulation Government can moderate influence Brand Image against Purchase Interest, Regulation Government No can moderate influence Price to Purchase interest.